Incidence of recreational snowboarding-related spinal injuries over an 11-year period at a ski resort in Niigata, Japan - Noboru Hosaka; Katsumitsu Arai; Hiroshi Otsuka; Hidefumi Kishimoto (BMJ Open Sport & Exercise Medicine)
Background There is limited knowledge regarding the incidence of recreational snowboarding-related spinal injuries.Objective This study investigated the incidence and characteristics of recent recreational snowboarding-related spinal injuries and discussed possible preventive measures to reduce the risk of spinal injuries.Methods This descriptive epidemiological study was conducted to investigate the incidence and characteristics of snowboarding-related spinal injuries at the Myoko ski resort in Niigata Prefecture, Japan, between 2006 and 2017. The incidence of spinal injuries was calculated as the total number of spinal injuries divided by the number of snowboarding visitors, which was estimated based on the ticket sales and estimates regarding the ratio of the number of skiers to the number of snowboarders reported by seven skiing facilities.Results In total, 124 (72.5%) males and 47 (27.5%) females suffered spinal injuries. The incidence of spinal injuries was 5.1 (95% CI 4.4 to 5.9) per 100 000 snowboarder visitors. Jumps at terrain parks were the most common factor in 113 (66.1%) spinal injuries, regardless of skill level (29/49 beginners, 78/112 intermediates, 6/10 experts). Overall, 11 (including 9 Frankel A) of 14 (78.6%) cases with residual neurologic deficits were involved with jumps.Conclusions In recreational snowboarding, jumping is one of the main causes for serious spinal injuries, regardless of skill level. The incidence of spinal injuries has not decreased over time. Individual efforts and educational interventions thus far have proven insufficient to reduce the incidence of spinal injury. Ski resorts and the ski industry should focus on designing fail-safe jump features to minimise the risk of serious spinal injury.